1971
DOI: 10.1192/bjp.119.550.253
|View full text |Cite
|
Sign up to set email alerts
|

Depression Across Cultures

Abstract: Comments have been frequently made on the differences in the symptomatological pattern of depression in different cultural groups. Kraepelin (1921), in his study on the incidence of depressive illness in Asian countries, mentioned that depression in Java was characterized almost exclusively by excitement and confusion and that ideas of sin and suicidal tendencies were absent. Carothers (1958) could not elicit feelings of guilt or self abasement in depression among the Africans of Kenya. Lambo (1956), of Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…The World Health Organization multicountry study demonstrated that primary care physicians in their study centres detected only half of all cases of depression (Sartorius et al, 1996). Treatmentseeking for depressive symptoms is relatively rare in many non-western societies and among immigrant and ethnic minority groups in the west (Patel, 2001;Teja et al, 1971;Sue et al, 1994;Swartz et al, 1994).…”
Section: Using Depression Screening Tools In a Global Contextmentioning
confidence: 99%
“…The World Health Organization multicountry study demonstrated that primary care physicians in their study centres detected only half of all cases of depression (Sartorius et al, 1996). Treatmentseeking for depressive symptoms is relatively rare in many non-western societies and among immigrant and ethnic minority groups in the west (Patel, 2001;Teja et al, 1971;Sue et al, 1994;Swartz et al, 1994).…”
Section: Using Depression Screening Tools In a Global Contextmentioning
confidence: 99%
“…In a study on 100 patients diagnosed with depression, Teja and colleagues reported that insomnia and anxiety were common symptoms in their study population [15] . Somatic symptoms have been fairly commonly reported in patients with depression, especially in the Indian scenario.…”
Section: Dr Priya Vijayakumar Et Al / a Study Of The Prevalence Of Dmentioning
confidence: 99%
“…Despite the fact that the 21-item HRSD is an established instrument also in transcultural studies on depres-sion [22,[82][83][84], our paper points to demands for adaptations to improve its applicability in such investigations: (1) for the assessment of the whole spectrum of ethical feelings, the HRSD needs an additional item for shame; (2) the definitions of feelings and delusions of guilt are lacking in (psychopathological) precision, and (3) the same holds good for the differentiation between hypochondriac anxiety and delusions. Moreover, proper ethnolinguistic studies could provide the basis for the development of special instruments for transcultural studies beyond the HRSD.…”
Section: Existence Of Depressive Delusions Of Guilt Only In Austriamentioning
confidence: 99%